The phylogenetic relationships of the Fanniidae within the muscoid grade (Diptera: Calyptrata) based on the musculature of the male terminalia - Sorokina, Vera S. (Insects)
Simple Summary The Fanniidae is a small dipteran family in the muscoid grade of the Calyptrata. To resolve controversial issues of phylogeny, in addition to molecular analyses, the study of the muscles of the pregenital and genital segments of males can significantly help because they are considered to provide important information relating to the phylogenetic branching of the Cyclorrhapha. Here, the authors report on the structure of the sclerites and the muscles of terminal segments of three species of the Fanniidae. These structures are compared with other members of the muscoid grade, as well as the Oestroidea and Hippoboscoidea. In comparison with the majority of the Calyptrata, there is a significant reduction of the sclerites and muscles of the pregenital segments of the male genitalia of the Fanniidae. The presence of the lateral bacilliform sclerites, as well as the presence and position of the epandrial muscles of the Fanniidae as in primitive Muscidae and also in Tachina and Calliphora, is best interpreted as a plesiomorphic state, while the reductions are considered as derived relative to the ground plan of the Calyptrata. The abdominal and pregenital segments and the genitalia were studied in males of Fannia subpellucens (Zetterstedt, 1845), Fannia canicularis (Linnaeus, 1761) and Fannia incisurata (Zetterstedt, 1838). In comparison with the remaining members of the muscoid grade, in addition to the symmetry of the pregenital segments, significant reductions of the sclerites and musculature of the male terminalia have been observed in Fanniidae. The muscular structure of pregenital segments confirms that the fused pregenital ring is syntergosternite VI + VII + VIII. Symmetry and fusion, as well as the lower number of the sclerites and muscles of the pregenital segments and male genitalia of the Fanniidae, can be considered apomorphic character states. The presence of the lateral bacilliform sclerite, as well as the presence and position of the epandrial muscles M 26, three pairs of muscles M 19 and paired muscles M 18, can be considered as a plesiomorphic character state of the Fanniidae. The structure of the sclerites and muscles of the male abdominal segments and terminalia place the Fanniidae at the base of the muscoid grade and Oestroidea, as has been confirmed by recent molecular studies.